Perancangan Proses Bisnis Menggunakan UML Berdasarkan Fit/Gap Analysis Pada Modul Inventory Odoo - Sukmawati, Riska; Priyadi, Yudi (INTENSIF: Jurnal Ilmiah Penelitian dan Penerapan Teknologi Sistem Informasi, 2019)
The company's information system that currently mainstay is Enterprise Resource Planning (ERP). The different data systems and real data at PT OTKA and Odoo make the company need to evaluate so that the gap does not continue. This study uses Fit/Gap Analysis which is used to compare whether the system is in line with company expectations, and then Failure Mode Effect Analysis (FMEA) to obtain the Risk Priority Number (RPN) level. The evaluation results of a system evaluation described by the Unified Modeling Language and mockup User Interface. The research data uses primary and secondary data. The data validity uses the triangulation method. The results of this study are PT OTKA has not implemented the Odoo maximally because the percentage of Gap is greater than the Fit. After risk analysis, two processes with the highest RPN, each of it is 448, which is updating the inventory of goods in and out automatically. So recommendations for companies are the result of special processes and actors who can monitor each goods transfer.